PERBEDAAN USAHATANI PADI SEHAT DAN PADI KONVENSIONAL (Oryza sativa L.) DI KECAMATAN PANDAK, KABUPATEN BANTUL - Ineka Wedhari Amipurba; Susi Widiatmi (Fakultas Pertanian UST, 2018)
The research was carried out in Pandak district, Bantul regency with the purpose to know the differences of income as well as the feasibility of farming of rice and conventional rice healthy. The hypothesis proposed income eligibility and suspected of farming rice healthy higher compared with conventional rice farming. The method of determining the location of research done in a purposive sample, the determination of healthy rice farmers used the census method with the total sample, the determination of conventional rice farmers used proportional random sampling method with the total sample of 30. The research method used is descriptive analysis method, analysis of revenues and R/C ratio, as is descriptive as well as statistical test. Of the results showed that: (1) Average median income healthy and conventional rice farmers amounted to IDR19.395.841,00 and IDR12.616.460,00. (2) The value of R/C ratio healthy and conventional rice farming of 3,2 and 2,4.